Mediating effect of work environment on the relationship between safety management practices and safety performance among nurses of public hospitals in Jordan - Abuashour, Abdallah Mohammad Barakat (2020)
Based on the Social Exchange Theory, this study examined the role of the work environment in mediating the relationship between safety management practices on the self-reported safety performance of nurses (safety compliance, safety participation and risky behaviour). A total of 517 nurses from eight hospitals belonging to the Jordanian Ministry of Health in Irbid participated in the study. Partial Least Squares (PLS) and the Structural Equation Modelling techniques were used to test the hypotheses. The results found that safety management practices directly impact safety compliance, safety participation, and risky behaviour. Furthermore, work environment was found to be a mediating factor in the relationship between safety management practices, safety compliance and safety participation. However, work environment did not have a mediating effect on the relationship between safety management practices and risky behaviour among the respondents. Thus, from the findings of the study, it can be concluded that the hospital management should focus on implementing safety management practices and consider the work environment of nurses when making decisions on how to improve their safety performance. Finally, the theoretical and practical implications of the study are discussed.